Enhancing STEAM education through augmented reality: the EduAR open platform experience - Velarde-Camaqui, Davis; Celaya-Ramírez, Rosario; Contreras-Fuentes, Yéssica; Sanabria-Z, Jorge (Frontiers in Education, 2024)
Quality education is pivotal for fostering innovation and development, with Augmented Reality (AR) offering transformative learning experiences. The absence of open-access platforms for AR resources hinders the democratization of educational technology. This study introduces EduAR, an open-access platform designed to provide validated AR resources for STEAM education, aiming to enhance learning processes and promote equitable access to quality education. Employing a mixed-methods approach, the platform’s usability was assessed using the System Usability Scale (SUS), where it achieved a high usability score, highlighting its user-friendliness and effectiveness. Additionally, qualitative feedback through focus groups provided insights into the platform’s impact on learning engagement and skill development. The study yielded the following findings: (a) Incorporating AR in STEAM disciplines through an open validated platform is an effective strategy for enriching learning and teaching processes; (b) The EduAR platform allows effective adoption due to its high usability and accessibility; (c) Design-Based Research is useful when looking to improve an AR educational platform; (d) EduAR is a valuable tool for providing equitable access to quality educational resources; and (e) EduAR promotes problem-solving and critical thinking among students. This comprehensive research underscores the potential of EduAR in enhancing educational outcomes, establishing a solid foundation for future advancements in educational technology and open educational resources (OER). Its benefit is foreseen for both teachers and researchers interested in the implementation of AR in courses within the framework of openness.